Analisis Kualitas Website Dinas XYZ dengan Menggunakan Pendekatan ISO/IEC 9126 Untuk Mendukung Continuous Improvement Layanan Publik - Suluh Hidayat; Heni Candra Kirana; Aji Supriyanto (LPPM Institut Pendidikan Nusantara Global, 2026)
The rapid development of e-government initiatives is driving the need for quality public digital services, particularly websites that serve as the primary gateway for information access and administrative interaction. This study aims to evaluate the software quality of the XYZ Department Website using the ISO/IEC 9126 framework and identify aspects that require improvement to support continuous improvement. The evaluation was conducted on six quality attributes: Functionality, Reliability, Usability, Efficiency, Maintainability, and Portability. The study used a quantitative approach through the distribution of Likert-scale questionnaires to 15 respondents, accompanied by direct observation of the system and review of technical documentation. The results showed that all attributes received a